ANALISIS PROFESIONALISME GURU BAHASA ARAB DI MA HIDAYATULLAH YOGYAKARTA - Ismail; Bakri Muhammad Bakheit Ahmed; Zeid B. Smeer (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the professionalism of Arabic language teachers at MA Hidayatullah Yogyakarta. It employed a qualitative approach with a single case study design. Data were collected through observations, interviews, and document analysis involving the principal, the vice principal for curriculum affairs, and Arabic language teachers. Data were analyzed using the Miles and Huberman interactive model, which consists of data reduction, data display, and conclusion drawing. The findings indicate that the Arabic language teachers have demonstrated the four core teacher competencies, namely pedagogical, personal, social, and professional competencies, at a good level. The teachers were able to create a conducive learning environment, integrate Islamic values (tauhid) into the teaching and learning process, foster collaboration among teachers, and demonstrate adequate mastery of the subject matter in accordance with students' learning needs. However, several aspects still require improvement, including the consistent implementation of lesson plans, the application of diagnostic assessment, the integration of educational technology, participation in professional organizations, and the strengthening of professional networks. Therefore, continuous professional development is essential to enhance the quality of Arabic language teaching and to support the successful implementation of the Bi'ah Lughawiyah (Arabic Language Environment) program at MA Hidayatullah Yogyakarta